The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1108/ecam-01-2012-0007
|View full text |Cite
|
Sign up to set email alerts
|

Using a case study approach to identify critical success factors for alliance contracting

Abstract: Purpose – There has been a significant increase in the use of relationship contracting in the global construction industry, with strategies such as Partnering, Alliancing and Public-Private Partnerships all used. These approaches were introduced to the Australian construction industry in the 1990s in an attempt to overcome the adversarial nature of traditional contracting methods. The purpose of this paper is to investigate factors that influence the successful implementation of Project Allianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 19 publications
0
50
0
Order By: Relevance
“…A project alliance model can be perceived through three main dimensions: 1) management and support, 2) collaboration, and 3) knowledge and sharing (Love et al, 2010), or five key features: 1) joint liability and organization, 2) joint decision-making and problem-solving, 3) open-book communication, 4) teambuilding, meeting, and workshops, and 5) monitoring performance and job satisfaction (Fernandes et al, 2017). However, to illustrate the operational aspect of the project alliance model, more descriptive mechanisms-referred to either as principles (Ross, 2003), characteristics (Lahdenperä, 2012), indicators (Ibrahim et al, 2013), or critical success factors (Hietajärvi et al, 2017b;Jefferies et al, 2014;Love et al, 2010)-are shown below in Table 1.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A project alliance model can be perceived through three main dimensions: 1) management and support, 2) collaboration, and 3) knowledge and sharing (Love et al, 2010), or five key features: 1) joint liability and organization, 2) joint decision-making and problem-solving, 3) open-book communication, 4) teambuilding, meeting, and workshops, and 5) monitoring performance and job satisfaction (Fernandes et al, 2017). However, to illustrate the operational aspect of the project alliance model, more descriptive mechanisms-referred to either as principles (Ross, 2003), characteristics (Lahdenperä, 2012), indicators (Ibrahim et al, 2013), or critical success factors (Hietajärvi et al, 2017b;Jefferies et al, 2014;Love et al, 2010)-are shown below in Table 1.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A high degree of commitment leadership from the alliance board and management is required in order to inspire the development of a collaborative and participative culture as well as influence the intensity of the integration process towards best for project (McCormick, 2010;Mills et al, 2012). Forming an integrated office is critical for project teams to enhance and improve their interaction and collaboration in real time ( Jefferies et al, 2014). Finally, in relation to free flow communication, several scholars (e.g.…”
Section: Summary Of Sevenmentioning
confidence: 99%
“…The alliance theme has also generated much doctoral research (Davis, 2005;Davies, 2008;Sweeney, 2009;MacDonald, 2011;Chen, 2013;Vilasini, 2014;She, 2014;Ibrahim, 2014). Related study in general has focussed on finding the success factors of the alliance ( Jefferies, Brewer and Gajendran, 2014;Mistry and Davis, 2009). These studies also emphasise the characteristics of the alliance which some other research efforts have attempted to define (Chen and Manley, 2014;Walker and Lloyd-Walker, 2015;Chen et al, 2012).…”
Section: Present Knowledgementioning
confidence: 99%